Autistic thinking, scripture and church: a qualitative case study and proposal - Rapley, Stewart (Practical theology, 2021)
In this article I propose that autistic cognitive ‘distinctives’ may give rise to differences in understanding of the Bible, with implications for the church. Through a survey of available literature, I have concluded that there is little help available in how to support the cognitive engagement with their churches of adult autistic worshippers who do not have learning difficulties. Using a qualitative case-study of nine adult autistic worshippers, I explore ways in which the participants’ understanding of, and approach to, the Bible differ from those of their churches and congregations, the resulting level of risk to cognitive engagement with their churches, and their mitigation of this risk. In the present paper I discuss my findings from this study. Finally, I use suggestions made by study participants to formulate outline requirements for a potential Prototype Engagement Model for churches as a starting point for dialogue. These recommendations include proposals for deepening a church’s understanding of autism and ways of providing help with Biblical interpretation and application, together with support for ‘talking through’ concerns arising within an autistic context.